Criminological Examination of The Premeditated Murder Perpetrated by Richard Eliezer in Case Law Number 798/Pid.B/2022/PN JKT.SEL - Adzholla Hadzna Sungkar; Amanda Regina Pallas Heriman; Caroline Caroline; Muhammad Afif Efendi (Universitas Pelita Harapan, 2023)
Murder cases in Indonesia often occur but there is one murder case committed by law enforcers. This harms the public view of law enforcement officials. On the other hand, we must be able to see this murder case from the perspective of the murderer, one of whom is Richard Eliezer in the murder case of Brigadier Joshua Hutabarat. Richard Eliezer was a policeman who killed another policeman, Joshua. In this murder we must be able to see from different perspectives such as the perspective of psychology, sociology and society so that everyone can judge whether the penalty that Richard Eliezer recevied was proper or not. The purpose of this research is to examine from the criminological perspective the premeditated murder perpetrated by law enforcement officers against their aides who should be under their guidance. The methodology used is normative, reinforced by primary data, especially in the material of Court Decision no. 798/Pid.B/2022, statements from witnesses in this premeditated murder case. Then, analyze with secondary data and the law system in the police. It is found that psychology of abuse of power often involves analyzing the motivations and behaviors of individuals who abuse power, as well as the factors that influence and prevent such behavior related to the penalty imposed in the case law, seen from perspectives such as the psychology, sociology and society.